PENGARUH LOKASI, RASA, DAN CIRI KHAS TERHADAP LOYALITAS KONSUMEN GUNA MENINGKATKAN KEPUTUSAN PEMBELIAN PADA MAKANAN KHAS DI KABUPATEN SELUMA DESA AIR TERAS - Durisa, Anugrah; Sismanto, Adi (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2024)
This study is entitled The Influence of Location (X1), Taste (X2), Characteristics (X3) on Consumer Loyalty (Y) in order to increase Consumer Purchase Decisions (Z) on Typical Foods in Seluma Regency, Air Teras Village, it can be concluded that Location  affects Consumer Loyalty, Taste affects Consumer Loyalty, Characteristics affect Consumer Loyalty, Consumer Loyalty affects Purchase Decisions in using products. Location indirectly affects  the Purchase Decision in using the product. Rasa has an indirect effect on the Purchase Decision in using the product. Characteristics have an indirect effect on Purchase Decisions Keywords: Location, Taste, Characteristics, Consumer Loyalty, Purchasing Decisions